PROBLEMS AND SOLUTIONS TO PROTECT THE YOUNG GENERATION FROM FOREIGN IDEAS - Munavvarkhanova Makhliyokhan Muzaffarkhan kizi; Mirzaakhmedova Khumora Turdimamat kizi (Scholar Express Journals, 2022)
In this article, in today's age of information technology, some of our young people are going in the wrong direction, the opportunities created in our country for the younger generation and their use, the President's views on youth, the high confidence in them, 'Thoughts on ideas and suggestions for the prevention of mysteries are stated.
Keywords: Young generation; foreign ideas; modern information technologies; 5 important initiatives